The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s11666-023-01534-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Droplet Impact on the Substrate with Surface Preparation in Thermal Spraying with SPH

Abstract: The properties of thermally sprayed coatings depend heavily on their microstructure. The microstructure is determined by the dynamics of the impact of the droplets on the substrate surface and the subsequent overlapping of the previously solidified and deformed droplets. Substrate preparation prior to spraying ensures strong adhesion of the coating. This includes roughening and preheating of the substrate surface. In the present study, the smoothed particle hydrodynamics (SPH) method is used to model the Al2O3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This includes having direct access to the neighborhood search needed for an efficient evaluation of the ray tracer. Additionally, since SPlisHSPlasH has already been used in the process simulations of tungsten inert gas welding (TIG) and thermal spraying, the temperature and fluid simulation can be leveraged for a full process simulation in future [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes having direct access to the neighborhood search needed for an efficient evaluation of the ray tracer. Additionally, since SPlisHSPlasH has already been used in the process simulations of tungsten inert gas welding (TIG) and thermal spraying, the temperature and fluid simulation can be leveraged for a full process simulation in future [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…For the subsequent process simulation, smoothed particle hydrodynamics has been shown to be well applicable to the simulations of heat and mass transfer needed in welding engineering [6][7][8][9][10][11]. Due to the meshless, Lagrangian nature of smoothed particle hydrodynamics, it conserves mass by construction and eases the treatment of topological changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of the authors' knowledge, there are no reported studies on the application of smoothed particle hydrodynamics for any variant of digitally controlled gas metal arc welding simulations. Given the potential advantages that smoothed particle hydrodynamics can offer, such as its ability to handle large deformations and free surfaces, it presents a promising avenue for future research [14,15]. The exploration and development of smoothed particle hydrodynamics for bidirectional wire control techniques simulations could provide insights that further enhance the comprehension of this exceptional technology and its applications.…”
Section: State Of the Artmentioning
confidence: 99%
“…Thus, the derivative of a quantity is formed by the derivative of the kernel function [7,8]. The presented model is built upon the bases developed for TIG welding and droplet impact in thermal spraying [11,14].…”
Section: Model Descriptionmentioning
confidence: 99%
“…The dynamics of droplet impact play a pivotal role in various industrial processes, ranging from inkjet printing [1] to spray coating [2] and combustion [3]. Understanding the intricate interplay between droplet behavior and the surrounding environment is essential for optimizing these processes and developing innovative technologies.…”
Section: -Introductionmentioning
confidence: 99%